Social Construction of The Elite in The Quran (Analysis of Term Al-Mala’) - Muhammad Yusuf; Mardan Mardan; Nahdhiyah Nahdhiyah; Kamaluddin Nurdin Marjumi (Institut Agama Islam Negeri Madura, 2021)
From a sociohistorical-anthropological perspective, the existence of an elite class with a class of people is known in the Qur’an. This research elaborates the verses of the Qur’an about elite society in social order. The existence of an elite society and its role in human civilization is the main concern in this study. Through the thematic interpretation method, typology and the role of elite society are explained. The terms prophet, apostle, malik, and al-mala’ refer to the elite. Prophets and messengers are elite groups based on revelation, malik based on political power relations. The term al-mala’ is part of an elite society divided into three groups, namely al-mala’, which opposes the apostles, al-mala’, which does not oppose the da’wah of the apostles, and al-mala’ which has a hypocritical character. Da’wah and education carry the regeneration mission for the birth of new elites who are partners in the benefit. As for the opponents of da’wah and the elite who are hypocritical in character, they must be anticipated so as not to cause chaos, crisis, and crime.